An Evaluation of change management strategies on organisational performance. A case study of Premier Service Medical Aid Society (PSMAS) - Munyawarara, Vitos (BUSE, 2023)
This case study aims to evaluate the impact of change management strategies on the organizational performance of Premier Service Medical Aid Society (PSMAS). The study focuses on PSMAS as a case organization and examines the change management strategies implemented during a period of organizational change. The research adopts a qualitative research approach, collecting primary data through interviews with key stakeholders involved in the change management process, including senior management, employees, and customers. Additionally, secondary data from organizational documents and performance indicators are analysed. The evaluation assesses the effectiveness of the change management strategies in various dimensions of organizational performance, such as financial performance, employee satisfaction, customer satisfaction, and operational efficiency. The study also identifies challenges and obstacles encountered by PSMAS during the change management process and analyses their impact on organizational performance. Based on the findings, the study provides recommendations for enhancing change management practices and improving overall organizational performance. The insights gained from this case study contribute to the existing knowledge on change management and its influence on organizational performance, specifically within the context of PSMAS and the healthcare industry.
Keywords: Change management; Organizational performance; Healthcare management; Medical aid societies